A Point Mutation of the Alpha-Tubulin Gene ClTUA Causes Dominant Dwarf Phenotype in Watermelon (Citrullus lanatus) - Ziwei Hu; Leichen Zhang; Jun Shi; Quansheng Ying; Huafeng Zhang; Xingping Zhang; Yun Deng; Yuhong Wang (Horticulturae, 2025)
Vine length is a crucial plant architecture trait in watermelon, which determines its height. In this study, we identified a dominant dwarf watermelon mutant by treating G42 with Ethyl methanesulfonate (EMS). In order to clarify the causes of the dwarfism in mutants, genetic statistics, phenotypic observation, and cytological observation were carried out. Meanwhile, individual resequencing combined with molecular markers was used to map the candidate gene. Our results demonstrated that the dwarf mutant exhibited incomplete dominance. The dwarf plants showed a decrease in the number of internodal cells, shortened internodes, and reduced vine length. Gene mapping indicated that the target gene responsible for this mutation was ClTUA, which encodes α-tubulin. A point mutation in the dwarf plants was identified, specifically, a change from C to T at the 1851st base pair. Further experiments, including transcriptome analysis and Liquid Chromatography–Tandem Mass Spectrometry (LC-MS/MS), revealed that this gene mutation affected auxin synthesis, leading to the dwarfing of the plants. This study provides new germplasm resources and a theoretical foundation for plant architecture breeding in watermelon.